Teoria – empiria – praktyka. Status metodologiczny nauk społecznych - Banaszak, Sławomir (Studia Edukacyjne, 2017)
The mutual relations between theory (seen as a set of theoretical statements) and empiricism is of special importance, especially in pedagogics. Why? Since pedagogics is immersed in practice, everyday reality and the mundane. The author focuses his reflections on the observation of an insufficient use of the theoretical potential by contemporary social sciences. Obviously, this is accompanied by the insufficient use of the research potential, which in turn deepens the stagnation in the field of theory. The author takes into account the classical approaches to theory with its relations with empiricism and moreover indicates contemporary exemplifications of this state of affairs. He moreover claims that research results are inadequately linked to theoretical reflection and indicates the similarities and differences in this respect in the field of social sciences.